Goal disturbance in early-stage breast cancer survivors. Issue 4 (4th July 2019) - Haydon, Marcie D.; Stanton, Annette L.; Ganz, Patricia A.; Bower, Julienne E.
Abstract: Purpose: Cancer-related goal disturbance can influence long-term outcomes in cancer patients and survivors; however, few studies have examined the factors that contribute to goal disturbance in early survivorship. Design: The current study examined the relationships between demographic variables, cancer- and treatment-related factors, and behavioral and psychological symptoms (i.e., fatigue, pain, cognitive complaints, depressive symptoms, and anxiety) and goal disturbance in breast cancer survivors 1 year after treatment completion. Methods: Women diagnosed with early-stage breast cancer ( n = 171) completed assessments following primary treatment (i.e., surgery, radiation, and chemotherapy) and again 6 months and 1 year later. We focused on the 1-year post-treatment assessment when participants were asked if they had experienced a cancer-related goal disturbance. Findings: Approximately, 27% of women reported a cancer-related goal disturbance. Analyses indicated that both receipt of chemotherapy and behavioral and psychological symptoms—analyzed as a composite score and individually—were associated with a higher probability of reporting a goal disturbance. Conclusions: Chemotherapy and behavioral and psychological symptoms were unique correlates of goal disturbance, suggesting that the impact of chemotherapy extends beyond its influence on persistent symptoms. Implications: Elucidating factors that inhibit the pursuit of meaningful activities in early survivorship is critically important to understanding the long-term psychosocial impacts of cancer diagnosis and treatment.